The effect of a Stroop-like task on postural control in dyslexic children. - Maria Pia Bucci (Public Library of Science (PLoS), 2013)
The influence of a secondary task on concurrent postural control was explored in twenty-one dyslexic children (mean age: 10.4 ± 0.3 years). Data were compared with twenty age-matched non-dyslexic children. As a secondary task, a modified Stroop test was used, in which words were replaced with pictures of fruits. The postural control of children was recorded in standard Romberg condition as the children were asked to name the colour of fruits appearing consecutively on a computer screen. Two conditions were tested: a congruent condition, in which the fruit was drawn in its natural ripe colour, and a non-congruent colour condition (NC), in which the fruit was drawn in three abnormal colours. A fixating condition was used as baseline. We analyzed the surface, length and mean speed of the center of pressure and measured the number of correct responses in the Stroop-like tasks. Dyslexic children were seen to be significantly more unstable than non-dyslexic ones. For both groups of children, the secondary task significantly increased postural instability in comparison with the fixating condition. The number of correct responses in the modified Stroop task was significantly higher in the non-dyslexic than in the dyslexic group. The postural instability observed in dyslexic children is in line with the cerebellar hypothesis and supports the idea of a deficit in automatic performance in such children. Furthermore, in accordance with cross domain competition model, our findings show that attentional resources are used to a greater extent by the secondary task than in controlling body stability.